Comparison between blue ballpoint pen and blue gel pen inks using stereomicroscopy, video spectral comparator, atr-ftir, thin layer chromatography and chemometrics technique - Gannetion, Linthini (Universiti Sains Malaysia, 2016)
Pens have been used as tools to make alterations on documents during the act of forgery. The emergence of hybrid pen inks which exhibits both characteristics of gel pen and ballpoint pen inks has imposed challenges to ink discrimination. Therefore, this study aims to compare the physical and chemical characteristics of blue ballpoint pen inks and gel pen inks of similar hue through their ink profiles generated by four different techniques, namely microscopy, video spectral comparator (VSC), ATR-FTIR and thin layer chromatography (TLC). Ten blue ballpoint pens and ten blue gel pen inks were chosen randomly regardless of brands. Optical examination using stereomicroscope and VSC-6000, ATR-FTIR spectroscopy as well as thin layer chromatography using two different solvent systems were employed to analyse all ink samples. Results of ATR-FTIR and VSC microspectroscopy were statistically analysed using principal component analysis (PCA) and hierarchical cluster analysis (HCA) respectively to ease comparison and discrimination. The results show that the ink profiles of the pens which were created by combining the microscopical characteristics, fluorescent characteristics, FTIR spectra, ink solubility and combination of colourants used (dye or pigments) in gel pens and ballpoint pens vary despite the fact that all the pens visually appear to be of the same colour. This indicated that a combination of techniques provided better discrimination among the samples tested.